تحليل الدخل المزرعي والتكاليف الإنتاجية لتربية نحل العسل وكفاءة مشروعاتها في الساحل السوري - جحجاح محسن; عليو محمود; مكيس خالد; غوش محمد (Latakia University Journal -Biological Sciences Series, 2017)
أجريت الدراسة على عينة من المناحل في المنطقة الساحلية من سورية في عام 2013، وذلك من خلال استمارة أُعدت خصيصاً لهذا الغرض لعينة عشوائية قوامها 304 منحلاً. وقد هدف البحث إلى تحليل التكاليف الإنتاجية والدخل المزرعي وقياس مستوى الربحية والكفاءة الاقتصادية للمناحل. بيّنت النتائج بأن تربية نحل العسل تعدّ من المشاريع الزراعية المجدية اقتصادياً, حيث استطاعت معظم المناحل في العينة تحقيق صافي عائد موجب قدر وسطياً بنحو (405834) ل.س/منحل، بينما قدرت قيمته على مستوى الخلية بنحو (7120) ل.س. إذ تبين أن غالبية المناحل في عينة الدراسة (بنسبة 87.8%) استطاعت أن تحقق إيرادات موجبة، بينما تعرضت نسبة (12.2%) للخسارة محققة إيرادات سالبة. كما أشارت نتائج تقييم الاستثمار والتحليل المالي إلى الكفاءة الاقتصادية للمناحل المدروسة, إذ بلغ الهامش الإجمالي للخلية (11237.5) ل.س/سنة, ونسبة التكاليف إلى الإيراد (62.9%)، ونسبة الربح إلى التكاليف الكلية (59 %), والكفاءة الاقتصادية العامة (1.59), وفترة استرداد رأس المال (1.69) سنة. This study has been conducted on Syrian coastal area in 2013 season, aimed to analyze the cost of honey production and Farm income `at the Apiaries level, in addition to measure its net returns and economic efficiency. A field questioner was applied to obtain elementary data of a random sample consisted of (304) of Apiary units. The results show that beekeeping is one of the economically viable agricultural projects, where most of the apiaries in the sample were able to achieve a positive net return as much, on average, about (405 834) SP / promiscuous, while its value was estimated at the hive level by about (7120) SP. It was found that the majority of apiaries in the study sample (87.8%) were able to achieve positive earnings, While the ratio (12.2%) exposed of the loss, and realized negative revenues . The results of the investment evaluation and financial analysis showed to the economic efficiency of the apiaries , reaching gross margin of the hive (11237.5) SP/year, and ratio of costs to revenue (62.9%), the profit ratio to total costs (59%), and general economic efficiency (1.59 ), and the Payback period (1.69) years.